Maximilian Fuchs – Rob Cornelissen (ed.) EU Social Security Law, A Commentary on EU Regulations 883/2004 and 987/2009, Nomos/Hart Publishing (5 Nov. 2015) - József, Hajdú (Pécsi Munkajogi Közlemények, 2023)